Perceived Service Quality and the Marketing Mix Affecting the Hotels Customers’ Loyalty, Muang District, Nakhonsawan Province - Kritsana Dararuang กฤษณะ ดาราเรือง; Sittiporn Kao-un สิทธิพร เขาอุ่น; จงเกษกรณ์ เชาวฤทธิ์ (Dusit Thani College Journal, 2018)
The purposes of this research were to 1) study service quality, marketing mix and the hotels customers’ loyalty, Muang district, Nakhonsawan province; 2) study the relationship among service quality, marketing mix and hotels customers’ loyalty, Muang district, Nakhonsawan province; and 3) study important variables of service quality and marketing mix affecting the hotels customers’ loyalty, Muang district, Nakhonsawan province. The samples was customers’ hotels in Muang district, Nakhonsawan province, responded by 385 people. The following statistics were: means, standard deviation, pearson’s correlation coefficient and stepwise-multiple regression coefficient. It was found, from the research findings, that 1) Service quality, marketing mix and the hotels customers’ loyalty, Muang district, Nakhonsawan province were at a high level; 2) Service quality, marketing mix and the hotels customers’ loyalty were correlation with a statistically significance level of .05; and 3) Eleven major variables are affecting to the hotels customers’ loyalty, Muang district, Nakhonsawan province, with can explain variable or predict 48.20% of an dependent variable (customers’ loyalty) with significant level of .01